PENGARUH KOMITMEN ORGANISASI, ORIENTASI BERP RESTASI DAN EFFORT PADA KINERJA JABATAN DAN KEPUASAN KERJA - Siti Nurchasanah; Triyono Triyono; Ahmad Mardalis (Jurnal Manajemen Dayasaing, 2014)
The objective of this study is to analyze the inﬂuence of organizational commitment, achievement orientation and effort on job performance and job satisfaction. The total sample of 80 employees of PT Perkebunan Nusantara V (Persero) with purposive sampling. Based on the data analysis can be concluded that organizational commitment inﬂuences the job performance, as well as achievement orientation, achievement orientation inﬂuences the job performance. Meanwhile, the Effort does not have signiﬁcantly on the job performance. This is because at that time of the study of human resource management system associated with the consequence of Effort which has not been implemented. This condition is also inﬂuenced by individual effort which has not reﬂected the effort from all job performances, remembering job performance results obtained from group performance subvention. Organizational commitment signiﬁcantly has greater signiﬁcantly on job performance than achievement orientation. This study also found that job performance has inﬂuence on job satisfaction and job satisfaction has inﬂuence on organizational commitment.